Priorities for contraceptive method and service delivery attributes among adolescent girls and young women in Kenya: a qualitative study - Harrington, Elizabeth K.; Hauber, Brett; Ouma, Dismas Congo; Kimanthi, Syovata; Dollah, Annabell; Onono, Maricianah; Bukusi, Elizabeth A. (Frontiers in Reproductive Health, 2024)
Introduction: Despite increasing global commitment to meeting the family planning needs of adolescent girls and young women (AGYW), there is limited research on how they prioritize contraceptive method and service delivery characteristics. In this qualitative study, we examine the specific elements that drive the contraceptive choices of Kenyan AGYW, and apply our findings to the development of attributes and levels for a discrete choice experiment (DCE). Methods: Our four-stage approach included data collection, data reduction, removing inappropriate attributes, and optimizing wording. Between June-October 2021, we conducted in-depth interviews with 30 sexually-active, non-pregnant 15-24 year-old AGYW in Kisumu county, Kenya who desired to delay pregnancy. Interviews focused on priorities for contraceptive attributes, how AGYW make trade-offs between among these attributes, and the influences of preferences on contraceptive choice. Translated transcripts were qualitatively coded and analyzed with a constant comparative approach to identify key concepts. We developed and iteratively revised a list of attributes and levels, and pre-tested draft DCE choice tasks using cognitive interviews with an additional 15 AGYW to optimize comprehension and relevance. Results: In-depth interview participants' median age was 18, 70% were current students, and 93% had a primary sexual partner. AGYW named a variety of priorities and preferences related to choosing and accessing contraceptive methods, which we distilled into six key themes: side effects; effectiveness; user control; privacy; source of services; and cost. Bleeding pattern was top of mind for participants; amenorrhea was generally considered an intolerable side effect. Many participants felt more strongly about privacy than effectiveness, though some prioritized duration of use and minimizing chance of pregnancy above other contraceptive characteristics. Most AGYW preferred a clinic setting for access, as they desired contraceptive counseling from a provider, but pharmacies were considered preferable for reasons of privacy. We selected, refined, and pre-tested 7 DCE attributes, each with 2-4 levels. Conclusions: Identifying AGYW preferences for contraceptive method and service delivery characteristics is essential to developing innovative strategies to meet their unique SRH needs. DCE methods may provide valuable quantitative perspectives to guide and tailor contraceptive counseling and service delivery interventions for AGYW who want to use contraception.